2010
DOI: 10.1007/s10584-010-9962-y
|View full text |Cite
|
Sign up to set email alerts
|

The reluctance of resource-users to adopt seasonal climate forecasts to enhance resilience to climate variability on the rangelands

Abstract: As the impacts of climate-change on resource-dependent industries manifest, there is a commensurate effort to identify and implement strategies to reduce them. Yet, even when useful knowledge and tools exist, there can be poor adoption of adaptation strategies. We examine the reasons behind sub-optimal adoption of seasonal climate forecasts by graziers for managing climate variability. We surveyed 100 graziers in north-east Queensland, Australia and examined the influence of adaptive capacity, resource-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 80 publications
5
56
0
Order By: Relevance
“…In this study, low population sizes in St Helens and Bowen were also found to correspond to low natural (through past and current use) and human capital and higher resource dependence. Similar results have been found in studies focusing on rural resource dependent communities including graziers in northern Queensland (Marshall et al 2011) and rural and resource-based communities in Canada (McLeman et al 2011), where a reduction in resource dependence can enhance adaptive capacity. Another Canadian study found fishing dependent communities consistently had low in-migration, high rates of poverty and unemployment, and low family income and educational attainment (Stedman et al 2004).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this study, low population sizes in St Helens and Bowen were also found to correspond to low natural (through past and current use) and human capital and higher resource dependence. Similar results have been found in studies focusing on rural resource dependent communities including graziers in northern Queensland (Marshall et al 2011) and rural and resource-based communities in Canada (McLeman et al 2011), where a reduction in resource dependence can enhance adaptive capacity. Another Canadian study found fishing dependent communities consistently had low in-migration, high rates of poverty and unemployment, and low family income and educational attainment (Stedman et al 2004).…”
Section: Discussionsupporting
confidence: 85%
“…For example, the success of a community-led or industry-led initiative may depend on the support and capacity of individuals (Marshall et al 2012). Individuals that have a higher capacity to incorporate change into their working lives are more likely to effectively trade-off the short-term costs of change and future limitations on productivity (Marshall et al 2011). For these people, change may not be seen as a disturbance, but as an opportunity for the reorganization of resources, and for the renewal of their business's organization and activities (Darnhofer et al 2010).…”
Section: Adaptation and The Capacity To Adaptmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research findings have indicated the usefulness of weather forecasts for reducing vulnerability of rain-fed agriculture to drought, flooding and extremely low or high temperature [22][23][24][25][26]. Initiatives to promote access of African farmers to weather forecasts include formation of several regional Climate Outlook Forums (COFs) in the late 1990s [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…This illustrates the importance of understanding skill in user uptake of such products [6][7][8]. However, accuracy, lead time, and appropriate spatial and temporal scale of S2D climate forecast information may not be the main (or only) factors influencing user uptake; potential economic and environmental benefits may be of greater importance [9]. In addition, probabilistic (ensemble) prediction systems are more commonly used in medium-range applications, bringing additional challenges in communicating forecast information to end-users.…”
mentioning
confidence: 99%